Assessment on the information communication technology literacy among education managers as an expression of caring education - Cadiente , Arnie M.; Acob, Joel Rey; Bagon, Andres E. (Future Science, 2020)
The study determined assessment on the Information-Communications Technology literacy of school principals in Eastern Visayas Region, Philippines. This was conducted randomly selected central schools in thirteen (13) divisions in Department of Education. A total of 505 respondents, one hundred one (101) of whom were central school principals, 101 district supervisors and 303 teachers who rated the principal’s performance along the following indicators: Occupational Competence, Professional and Personal Competence, Attendance and Punctuality and Plus Factors. A survey questionnaire was used to gather the data relevant to the study. The obtained data were tabulated, analyzed, and interpreted through frequency counts, mean, percentage of distribution and t-test. Findings of the study were as follows: Of the 505 respondents, 65 (64.4%) were females while 36 (35.6%) were males, 53 (52.5%) belonged to early later years, 33 (32.7%) were masters’ and doctoral degree holders, 57 (56.5%) with actual monthly income of 36,501– 42,500, 40(48.51%) or almost half of the respondents has no ICT trainings, 49 (48.51%) owned computers for 1-3 years, 80 (79.21%) has 1-3 computer units, and 51 (50.5%) have favorable attitudes towards computer literacy. On the performance of principals as rated by teachers it was very satisfactory with a mean of 4.11 while immediate supervisors and principals themselves have a similar rating of very satisfactory with mean of 3.86 and 4.01 respectively. It is recommended that school principals must undergo continuing education program in relation to ICT. Literacy skills of school principals may lead to an effective instructions and managerial functions.